Two new species of the planthopper genus Flavina Stål (Hemiptera: Fulgoromorpha: Issidae) from China - Zhang, Yalin; Che, Yanli; Wang, Yinglun; Webb, M. D. (Zootaxa, 2010)
In the present paper, Flavina Stål is reviewed and a key to species is provided. Two new species, F. nigrifrons Zhang and Che, sp. nov., and F. nigrifascia Che and Wang, sp. nov., are described and illustrated, and F. hainana (Wang and Wang) is redescribed and illustrated, especially to show its male genitalia. The genus is compared to Fortunia Distant and comments are given on the family placement of the superficially similar genus Mahanorona Distant.